Diel regulation of photosynthetic activity in the oceanic unicellular diazotrophic cyanobacterium Crocosphaera watsonii WH8501 - Masuda, Takako; Bernát, Gábor; Bečková, Martina; Kotabová, Eva; Lawrenz, Evelyn; Lukeš, Martin; Komenda, Josef; Prášil, Ondřej (Environmental microbiology, 2018)
The oceanic unicellular diazotrophic cyanobacterium Crocosphaera watsonii WH8501 exhibits large diel changes in abundance of both Photosystem II (PSII) and Photosystem I (PSI). To understand the mechanisms underlying these dynamics, we assessed photosynthetic parameters, photosystem abundance and composition, and chlorophyll-protein biosynthesis over a diel cycle. Our data show that the decline in PSII activity and abundance observed during the dark period was related to a light-induced modification of PSII, which, in combination with the suppressed synthesis of membrane proteins, resulted in monomerization and gradual disassembly of a large portion of PSII core complexes. In the remaining population of assembled PSII monomeric complexes, we detected the non-functional version of the D1 protein, rD1, which was absent in PSII during the light phase. During the dark period, we also observed a significant decoupling of phycobilisomes from PSII and a decline in the chlorophyll a quota, which matched the complete loss of functional PSIIs and a substantial decrease in PSI abundance. However, the remaining PSI complexes maintained their photochemical activity. Thus, during the nocturnal period of nitrogen fixation C. watsonii operates a suite of regulatory mechanisms for efficient utilization/recycling of cellular resources and protection of the nitrogenase enzyme.
Keywords: chlorofyl a; fykobilizomy; tma; Cyanobacteria; sinice; Phycobilisomes; fotosystém I (proteinový komplex); Photosynthesis; Oceans and Seas; fixace dusíku; Photosystem II Protein Complex; oceány a moře; Nitrogen Fixation; fotosyntéza; fotosystém II (proteinový komplex); chlorofyl; Darkness; Chlorophyll A; Chlorophyll; Photosystem I Protein Complex